Iron-based catalyst as well as preparation method and application thereof
By grinding iron salt and coal powder, spraying alkali liquid for oxidation and drying, iron-based catalysts are prepared, which solves the complex preparation process and wastewater problems in the prior art, and achieves efficient and economical production of direct coal liquefaction catalysts.
Patent Information
- Application Number
- CN202510138853.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-07
- Publication Date
- 2025-04-08
AI Technical Summary
The preparation process of existing coal direct liquefaction catalysts is complicated, and it is easy to produce salt by-products and a large amount of salt-containing wastewater, and it is difficult to transport the reaction slurry.
Iron-based catalyst is prepared by mixing and grinding iron salt and coal powder, flattening, spraying alkali liquid evenly, and oxidizing and drying. This method reduces wastewater generation, realizes in-situ supported catalyst precursors, and avoids device blockage and generation of unloaded particles during the atomization of the slurry mixture.
The catalyst preparation process is simplified, water resource consumption and process wastewater treatment costs are reduced, catalyst production continuity and economicality are improved, and the conversion rate and oil yield of direct coal liquefaction reaction are improved.
Smart Images

Figure CN119771409A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of coal chemical industry, and specifically relates to an iron-based catalyst and a preparation method and application thereof. Background Art
[0002] Coal direct liquefaction refers to the process of converting coal from solid fuel to liquid fuel directly by reacting coal with hydrogen through hydrogenation cracking and removal of heteroatoms under high temperature and high pressure in the presence of catalysts and hydrogen-supplying solvents. Coal direct liquefaction technology is an effective way to cleanly utilize coal resources, and the liquid fuel produced by it can be used as a substitute for petroleum fuel.
[0003] Iron-based catalysts are inexpensive, have a wide range of raw materials, can be made into disposable catalysts, and have little impact on the environment during post-processing. They are widely used catalysts in the direct coal liquefaction process. One of the main methods for preparing iron-based catalysts for direct coal liquefaction is to use a salt solution containing iron ions to react with an alkaline solution. The prior art discloses the preparation of amorphous Fe(OH)2 or Fe(OH)3 ultrafine particles by mixing an iron salt solution with ammonia water, the particles generated by the reaction are dehydrated by high-speed centrifugation to form a hydrogel, the hydrogel is mixed and dispersed with an appropriate amount of coal powder and a liquefaction solvent to prepare a slurry iron-based catalyst; it also discloses the preparation of a coal slurry loaded with Fe(OH)2 by premixing a ferrous salt solution with coal powder, adding a certain amount of alkaline solution containing hydroxide ions to the mixture, stirring and mixing, the Fe(OH)2 is oxidized by air or oxygen to form γ-FeOOH, and the coal slurry is filtered to obtain a catalyst that can be used in a direct coal liquefaction process; it also discloses the preparation of a catalyst that can be used in a direct coal liquefaction reaction by first loading an iron-containing soluble salt solution onto a catalyst carrier by spraying, then using an alkaline aqueous solution to react with the iron salt loaded on the catalyst carrier, the reaction product undergoes a crystal phase transformation after being oxidized by air, and the catalyst that can be used in a direct coal liquefaction reaction is obtained. The above three catalyst preparation schemes require the use of a large amount of water in the production process, and a large amount of process wastewater will be generated during the subsequent treatment of the catalyst. The consumption of water resources and the treatment of process wastewater will increase the cost of the catalyst production process, thereby reducing the economic efficiency of the coal direct liquefaction process.
[0004] In addition, the prior art also discloses a slurry mixture formed by the reaction of an ammonia solution and a ferrous sulfate solution in a static mixer, and mixed with the coal powder in the absorption oxidizer, and then oxidized to undergo a crystal transformation to form a catalyst precursor, and the coal powder loaded with the catalyst precursor is dried and ground to obtain a coal direct liquefaction catalyst product. However, the use of this scheme to prepare the catalyst may cause the atomization device to be blocked during the atomization of the slurry mixture, thereby affecting the continuity of the catalyst production process, and the slurry mixture sprayed on the coal powder may also appear to be not loaded by the coal powder and aggregated into a larger particle catalyst. The prior art also discloses a catalyst preparation method using coal powder as a carrier, through an iron-based metal salt and an alkali at room temperature to prepare an iron-based oxygen (hydroxide) compound loaded on the surface of the coal powder, and using it as a catalyst for direct coal liquefaction reaction. The method uses a solid-phase reaction to prepare a catalyst, and the reactants may not be fully contacted due to insufficient reaction, resulting in a situation where the reaction cannot occur completely, and the catalyst mixture obtained by the reaction may have excess alkali, and because the reaction occurs between solids, the product may not be able to achieve full loading on the coal powder. Summary of the invention
[0005] The present application provides an iron-based catalyst and a preparation method and application thereof, aiming to solve the problems that the preparation process of existing direct coal liquefaction catalysts is complicated, salt by-products and a large amount of salt-containing wastewater are easily generated during the preparation process, and there is difficulty in transporting the reaction slurry.
[0006] The first aspect of the present application provides a method for preparing an iron-based catalyst, comprising the following steps:
[0007] (1) mixing iron salt and coal powder and grinding them to obtain a mixed powder;
[0008] (2) spreading the mixed powder evenly and spraying the alkali solution evenly on the spread mixed material to obtain a reaction material;
[0009] (3) The reaction material is subjected to an oxidative drying treatment to obtain the iron-based catalyst.
[0010] The preparation method described in the present application reduces the water production of wastewater in the step of loading coal powder with iron salt by grinding and dispersing iron salt with coal powder, sprays ammonia solution on the surface of the ground powder, and ammonia and ferrous sulfate can react to generate a catalyst precursor, and realize in-situ loading on the surface of coal powder. Since ferrous sulfate and ammonia react in extremely small droplets, a catalyst precursor structure with a particle size of hundreds of microns can be prepared. The main component of the prepared catalyst is FeOOH, which is easily converted into a pyrrhotite form that has a catalytic effect on the direct coal liquefaction process under the conditions of direct coal liquefaction, thereby promoting the direct coal liquefaction process.
[0011] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the iron salt includes one or more of FeSO4·7H2O, Fe2(SO4)3, Fe(NO3)2, Fe(NO3)3, FeCl2 and FeCl3.
[0012] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the mass ratio of the iron salt to the coal powder is 1:(1-5).
[0013] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the grinding temperature is 20-90° C., and the grinding time is 3-10 min.
[0014] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the particle size of the mixed powder is ≤200 mesh.
[0015] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the thickness of the mixed powder spread out is 0.1-1 mm.
[0016] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the molar ratio of the iron salt to the solute in the alkali solution is 1:(2-3).
[0017] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the alkali solution includes one or more of aqueous ammonia, aqueous sodium hydroxide solution, and aqueous potassium hydroxide solution.
[0018] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the mass concentration of the ammonia water is 3%-5%.
[0019] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the mass concentration of the sodium hydroxide aqueous solution is 0.01-0.10 g / L.
[0020] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the mass concentration of the potassium hydroxide aqueous solution is 0.01-0.12 g / L.
[0021] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, in step (3), the temperature of the oxidative drying is 35-95° C., and the time of the oxidative drying is 10-180 min.
[0022] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the method further comprises sequentially washing and drying the oxidized dried product.
[0023] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the washing liquid used in the washing is water.
[0024] According to some embodiments of the method for preparing the iron-based catalyst described in the present application, the drying temperature is 30-50° C., and the drying time is 1-2 hours.
[0025] The second aspect of the present application provides an application of an iron-based catalyst obtained by the preparation method described in the first aspect of the present application in direct coal liquefaction. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is a SEM image of the iron-based catalyst described in Example 1 of the present application;
[0027] Figure 2 This is the SEM image of the iron-based catalyst described in Comparative Example 2 of the present application. DETAILED DESCRIPTION
[0028] Embodiments of the present invention are described in detail below, and examples of the embodiments are shown in the accompanying drawings. The embodiments described below with reference to the accompanying drawings are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0029] In the present invention, the terms "one embodiment", "some embodiments", "examples", "specific examples", or "some examples" etc. mean that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the described specific features, structures, materials or characteristics may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0030] The present invention provides a method for preparing an iron-based catalyst, comprising the following steps:
[0031] (1) mixing iron salt and coal powder and grinding them to obtain a mixed powder;
[0032] (2) spreading the mixed powder evenly and spraying the alkali solution evenly on the spread mixed material to obtain a reaction material;
[0033] (3) The reaction material is subjected to an oxidative drying treatment to obtain the iron-based catalyst.
[0034] The preparation method described in the present application reduces the water production of wastewater in the step of loading coal powder with iron salt by grinding and dispersing iron salt with coal powder, sprays ammonia solution on the surface of the ground powder, and ammonia and ferrous sulfate can react to generate a catalyst precursor, and realize in-situ loading on the surface of coal powder. Since ferrous sulfate and ammonia react in extremely small droplets, a catalyst precursor structure with a particle size of hundreds of microns can be prepared. The main component of the prepared catalyst is FeOOH, which is easily converted into a pyrrhotite form that has a catalytic effect on the direct coal liquefaction process under the conditions of direct coal liquefaction, thereby promoting the direct coal liquefaction process.
[0035] In some embodiments of the present application, the iron salt includes one or more of FeSO4·7H2O, Fe2(SO4)3, Fe(NO3)2, Fe(NO3)3, FeCl2 and FeCl3.
[0036] In some embodiments of the present application, the mass ratio of the iron salt to the coal powder is 1:(1-5), for example, 1:1, 1:2, 1:3, 1:5, etc.
[0037] In some embodiments of the present application, the grinding temperature is 20-90°C, for example, 20°C, 25°C, 35°C, 50°C, 65°C, 73°C, 86°C, 90°C, etc., and the grinding time is 3-10min, for example, 3min, 5min, 7min, 10min, etc.
[0038] In some embodiments of the present application, the particle size of the mixed powder is ≤200 mesh, for example 250 mesh, 300 mesh, etc. The micron-sized ground powder can provide sufficient loading surface area for the generated catalyst precursor, and can also have a dispersing effect on the generated catalyst precursor, thereby avoiding the aggregation of the generated catalyst precursor.
[0039] In some embodiments of the present application, the thickness of the mixed powder is 0.1-1mm, such as 0.1mm, 0.2mm, 0.5mm, 0.8mm, 1mm, etc. The thickness of the ground powder should not be too thin. Too thin a thickness will make the coal powder fully wetted during the spraying of ammonia water, which is not conducive to the generation of the catalyst precursor loading on the coal powder surface; too thick a thickness will cause the ammonia water to not fully react with the iron salt in the ground mixture. When the thickness is within the range of the invention, a better loading and reaction effect can be obtained.
[0040] In some embodiments of the present application, the molar ratio of the iron salt to the solute in the alkali solution is 1:(2-3), for example 1:2, 1:2.2, 1:2.5, 1:3, etc. During the implementation process, an excess of ammonia water is used to ensure that the ammonia water fully reacts with the ferrous sulfate in the mixed powder.
[0041] In some embodiments of the present application, the alkali solution includes one or more of aqueous ammonia, aqueous sodium hydroxide solution and aqueous potassium hydroxide solution.
[0042] In some embodiments of the present application, the mass concentration of the ammonia water is 3%-5%, for example, 3%, 4%, 5%, etc.
[0043] In some embodiments of the present application, the mass concentration of the sodium hydroxide aqueous solution is 0.01-0.10 g / L, for example, 0.01 g / L, 0.03 g / L, 0.05 g / L, 0.08 g / L, 0.1 g / L, etc.
[0044] In some embodiments of the present application, the mass concentration of the potassium hydroxide aqueous solution is 0.01-0.12 g / L, for example, 0.01 g / L, 0.03 g / L, 0.05 g / L, 0.08 g / L, 0.1 g / L, 0.12 g / L, etc.
[0045] In some embodiments of the present application, in step (3), the temperature of the oxidative drying is 35-95°C, for example, 35°C, 40°C, 50°C, 60°C, 70°C, 90°C, 95°C, etc., and the time of the oxidative drying is 10-180min, for example, 10min, 20min, 30min, 50min, 60min, 100min, 120min, 180min, etc.
[0046] In some embodiments of the present application, the preparation method further comprises washing and drying the oxidized dried product in sequence.
[0047] By washing the oxidized dried product with a small amount of water and reusing the catalyst washing water, the salt substances generated during the catalyst preparation process can be removed and high-concentration salt-containing wastewater can be obtained. Ammonium salt by-products can be obtained by evaporating and concentrating the high-concentration salt-containing wastewater, cooling and crystallizing it.
[0048] In some embodiments of the present application, the washing liquid used for washing is water.
[0049] In some embodiments of the present application, the drying temperature is 30-50°C, such as 30°C, 40°C, 50°C, etc., and the drying time is 1-2h, such as 1h, 1.5h, 2h, etc.
[0050] In some embodiments of the present application, the preparation method further comprises grinding the product after washing and drying, and the particle size of the product obtained by grinding is 100-200 mesh.
[0051] The main component of the iron-based catalyst described in the present application is FeOOH.
[0052] The second aspect of the present application provides an application of an iron-based catalyst obtained by the preparation method described in the first aspect of the present application in direct coal liquefaction.
[0053] The technical solution of the present application is further described below in conjunction with specific embodiments and drawings.
[0054] Example 1
[0055] A method for preparing an iron-based catalyst comprises the following steps:
[0056] 12.50 g of FeSO4·7H2O and 12.50 g of raw coal powder were added into a ball mill and ground at 30°C for 5 min. The ground product was passed through a 200-mesh sieve to obtain a mixed powder.
[0057] The mixed powder is evenly spread on the reaction plane with a spreading thickness of 0.2 mm. A spray device (the spray device is a commercially available sprayer) is used to evenly spray 65 g of ammonia water with a mass concentration of 3.5% on the surface of the mixed powder to form a reaction material. The reaction material is placed in a convection drying oven and dried and oxidized for 3 hours at a temperature of 40°C. After the oxidation and drying process is completed, the product is washed with 30 mL of deionized water, the solid-liquid mixture is filtered, the filter cake is evenly spread, and dried in a 40°C oven to constant weight (for 1 hour), the dried filter cake is ground and passed through a 200-mesh sieve, and the obtained solid powder is an iron-based catalyst. The washing liquid is evaporated and concentrated and cooled and crystallized to obtain ammonium sulfate byproduct.
[0058] Example 2
[0059] The only difference between the preparation method of the iron-based catalyst described in Example 2 and that in Example 1 is that the mass ratio of iron salt to coal powder in the preparation method of the iron-based catalyst described in Example 2 is 1:3.
[0060] The specific steps include:
[0061] 6.25 g of FeSO4·7H2O and 18.75 g of raw coal powder were put into a ball mill and ground at 30°C for 5 min. The ground product was sieved through a 200-mesh sieve to obtain a mixed powder.
[0062] The mixed powder is evenly spread on the reaction plane with a spreading thickness of 0.2 mm. A spray device (the spray device is a commercially available sprayer) is used to evenly spray 33 g of ammonia water with a mass concentration of 3.5% on the surface of the mixed powder to form a reaction material. The reaction material is placed in a convection drying oven and dried and oxidized for 3 hours at a temperature of 40°C. After the oxidation and drying process is completed, the product is washed with 30 mL of deionized water, the solid-liquid mixture is filtered, the filter cake is evenly spread, and dried in a 40°C oven to constant weight (for 1 hour), the dried filter cake is ground and passed through a 200-mesh sieve, and the resulting solid powder is an iron-based catalyst. The washing liquid is evaporated and concentrated and cooled and crystallized to obtain ammonium sulfate byproduct.
[0063] Example 3
[0064] The only difference between the preparation method of the iron-based catalyst described in Example 3 and that in Example 1 is that the mass ratio of iron salt to coal powder in the preparation method of the iron-based catalyst described in Example 3 is 1:5.
[0065] The specific steps include:
[0066] 4.17 g of FeSO4·7H2O and 20.83 g of raw coal powder were put into a ball mill and ground at 30°C for 5 min. The ground product was sieved through a 200-mesh sieve to obtain a mixed powder.
[0067] The mixed powder is evenly spread on the reaction plane with a spreading thickness of 0.2 mm. A spray device (the spray device is a commercially available sprayer) is used to evenly spray 22 g of ammonia water with a mass concentration of 3.5% on the surface of the mixed powder to form a reaction material. The reaction material is placed in a convection drying oven and dried and oxidized for 3 hours at a temperature of 40°C. After the oxidation and drying process is completed, the product is washed with 30 mL of deionized water, the solid-liquid mixture is filtered, the filter cake is evenly spread, and dried in a 40°C oven to constant weight (for 1 hour), the dried filter cake is ground and passed through a 200-mesh sieve, and the obtained solid powder is an iron-based catalyst. The washing liquid is evaporated and concentrated and cooled and crystallized to obtain ammonium sulfate byproduct.
[0068] Example 4
[0069] The only difference between the preparation method of the iron-based catalyst described in Example 4 and that in Example 1 is that the mass ratio of iron salt to coal powder in the preparation method of the iron-based catalyst described in Example 4 is 1:4.
[0070] The specific steps include:
[0071] 5.00 g of FeSO4·7H2O and 20.00 g of raw coal powder were put into a ball mill and ground at 30°C for 5 min. The ground product was sieved through a 200-mesh sieve to obtain a mixed powder.
[0072] The mixed powder is evenly spread on the reaction plane with a spreading thickness of 0.2 mm. A spray device (the spray device is a commercially available sprayer) is used to evenly spray 27 g of ammonia water with a mass concentration of 3.5% on the surface of the mixed powder to form a reaction material. The reaction material is placed in a convection drying oven and dried and oxidized for 3 hours at a temperature of 40°C. After the oxidation and drying process is completed, the product is washed with 30 mL of deionized water, the solid-liquid mixture is filtered, the filter cake is evenly spread, and dried in a 40°C oven to constant weight (for 1 hour), the dried filter cake is ground and passed through a 200-mesh sieve, and the resulting solid powder is an iron-based catalyst. The washing liquid is evaporated and concentrated and cooled and crystallized to obtain ammonium sulfate byproduct.
[0073] Example 5
[0074] The only difference between the preparation method of the iron-based catalyst described in Example 5 and that in Example 2 is that in the preparation method of the iron-based catalyst described in Example 5, the temperature at which FeSO4·7H2O and raw coal powder are ground in the ball mill is 20°C, and the rest of the operations are the same as in Example 2.
[0075] Example 6
[0076] The only difference between the preparation method of the iron-based catalyst described in Example 6 and that in Example 2 is that in the preparation method of the iron-based catalyst described in Example 6, the temperature at which FeSO4·7H2O and raw coal powder are ground in the ball mill is 60°C, and the rest of the operations are the same as in Example 2.
[0077] Example 7
[0078] The only difference between the preparation method of the iron-based catalyst described in Example 7 and that in Example 2 is that in the preparation method of the iron-based catalyst described in Example 7, the temperature at which FeSO4·7H2O and raw coal powder are ground in a ball mill is 90°C, and the remaining operations are the same as in Example 2.
[0079] Comparative Example 1
[0080] The iron-based catalyst in Comparative Example 1 is commercially available analytically pure FeSO4·7H2O.
[0081] Comparative Example 2
[0082] The preparation method of the iron-based catalyst described in Comparative Example 2 comprises the following steps:
[0083] 6.25 g of FeSO4·7H2O and 18.75 g of coal powder were mixed in 50 mL of water, and 33 g of 3.5% ammonia water was gradually added to the mixture. After stirring and mixing, a coal slurry loaded with Fe(OH)2 was prepared, and then γ-FeOOH was formed after air oxidation.
[0084] Performance study of the iron-based catalysts described in Examples 1-7 of the present application and the iron-based catalysts described in Comparative Examples 1-2
[0085] Shenhua coal was used as the coal for liquefaction reaction, and 20 g of coal powder converted to anhydrous ash-free coal was used as the liquefaction reactant. The amount of catalyst added was calculated based on the iron content in the catalyst accounting for 1% of the mass of the anhydrous ash-free coal. The co-catalyst was sulfur, and its addition amount was calculated based on S:Fe=2:1 (atomic ratio). Tetralin was selected as the hydrogen supply solvent, and the amount of solvent added was calculated based on solvent:dry basis coal=55:45 (mass ratio). Under the conditions of hydrogen initial pressure of 10 MPa, reaction temperature of 450°C and reaction time of 120 min, the catalyst performance evaluation experiment was carried out in a 500 mL autoclave, and the results are shown in Table 2.
[0086] The coal direct liquefaction product was extracted and analyzed by n-hexane and tetrahydrofuran, and the gas product of the coal direct liquefaction reaction was analyzed by gas chromatography. The calculation process referred to GB / T 33690-2017 "Autoclave Test Method for Coal Liquefaction Reactivity".
[0087] The industrial analysis and elemental analysis data of the Shendong coal used are shown in Table 1:
[0088] Table 1
[0089]
[0090] Table 2
[0091]
[0092]
[0093] It can be seen from Table 1 that the data of the direct coal liquefaction catalyst prepared by the methods of Examples 1-7 in terms of conversion rate and oil yield are better than the corresponding data in Comparative Example 1. The data of the direct coal liquefaction conversion rate and oil yield of the catalyst prepared by the methods of Examples 1-4 are comparable to those of the catalyst in Comparative Example 2, but the direct coal liquefaction catalyst prepared by the methods of Examples 1-4 can simplify the catalyst preparation process and reduce the water consumption in the catalyst preparation process.
[0094] The SEM image of the iron-based catalyst described in Example 1 of the present application is as follows: Figure 1 As shown; the SEM image of the iron-based catalyst described in Comparative Example 2 is as follows Figure 2 shown.
[0095] from Figure 1It can be seen that the iron-based catalyst described in the present application is in the form of an elongated rod, with a radial length of 200-300nm and an axial length of 50-100nm. The catalyst prepared by the method described in Comparative Example 2 also has an elongated rod, with a radial length of 100-200nm and an axial length of 20-40mm. From the apparent morphology of the catalyst, it can be determined that the catalyst prepared in Example 1 and Comparative Example 2 is FeOOH. In the direct coal liquefaction reaction process, FeOOH can be converted into a catalyst active phase at a lower temperature, and catalyzes the direct coal liquefaction process.
[0096] Although the above embodiments have been shown and described, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations on the present invention. Changes, modifications, substitutions and variations of the above embodiments by those of ordinary skill in the art are all within the scope of protection of the present invention.
Claims
1. A method for preparing an iron-based catalyst, characterized in that: The following steps are involved: (1) mixing iron salt and coal powder and grinding them to obtain a mixed powder; (2) spreading the mixed powder evenly and spraying the alkali solution evenly on the spread mixed material to obtain a reaction material; (3) The reaction material is subjected to an oxidative drying treatment to obtain the iron-based catalyst.
2. The method for preparing an iron-based catalyst according to claim 1, characterized in that: The iron salt includes one or more of FeSO4·7H2O, Fe2(SO4)3, Fe(NO3)2, Fe(NO3)3, FeCl2 and FeCl3; And / or, the mass ratio of the iron salt to the coal powder is 1:(1-5).
3. The method for preparing an iron-based catalyst according to claim 1, characterized in that: The grinding temperature is 20-90°C; the grinding time is 3-10min; And / or, the particle size of the mixed powder is ≤200 mesh.
4. The method for preparing an iron-based catalyst according to claim 1, characterized in that: The thickness of the mixed powder is 0.1-1 mm.
5. The method for preparing an iron-based catalyst according to claim 1, characterized in that: The molar ratio of the iron salt to the solute in the alkali solution is 1:(2-3); And / or, the alkali solution includes one or more of aqueous ammonia, aqueous sodium hydroxide solution and aqueous potassium hydroxide solution.
6. The method for preparing an iron-based catalyst according to claim 1, characterized in that: The mass concentration of the ammonia water is 3%-5%; And / or, the mass concentration of the sodium hydroxide aqueous solution is 0.01-0.10 g / L; And / or, the mass concentration of the potassium hydroxide aqueous solution is 0.01-0.12 g / L.
7. The method for preparing an iron-based catalyst according to claim 1, characterized in that: In step (3), the temperature of the oxidative drying is 35-95° C., and the time of the oxidative drying is 10-180 min.
8. The method for preparing an iron-based catalyst according to claim 1, characterized in that: The preparation method also includes washing and drying the oxidized dried product in sequence.
9. The method for preparing an iron-based catalyst according to claim 8, characterized in that: The washing liquid used in the washing is water; And / or, the drying temperature is 30-50° C., and the drying time is 1-2 hours.
10. Use of the iron-based catalyst obtained by the preparation method according to any one of claims 1 to 9 in direct coal liquefaction.